Viral-Mediated Noisy Gene Expression Reveals Biphasic E2f1 Response to MYC - Wong, Jeffrey V.; Yao, Guang; Nevins, Joseph R.; You, Lingchong (Molecular cell, 2011)
Gene expression mediated by viral vectors is subject to cell-to-cell variability, which limits the accuracy of gene delivery. When coupled with single-cell measurements, however, such variability provides an efficient means to quantify signaling dynamics in mammalian cells. Here, we illustrate the utility of this approach by mapping the E2f1 response to MYC, serum stimulation, or both. Our results revealed an underappreciated mode of gene regulation: E2f1 expression first increased, then decreased as MYC input increased. This biphasic pattern was also reflected in other nodes of the network, including the miR-17-92 microRNA cluster and p19Arf. A mathematical model of the network successfully predicted modulation of the biphasic E2F response by serum and a CDK inhibitor. In addition to demonstrating how noise can be exploited to probe signaling dynamics, our results reveal how coordination of the MYC/RB/E2F pathway enables dynamic discrimination of aberrant and normal levels of growth stimulation. [Display omitted] ► Gene expression noise is an efficient means to probe dose responses ► Variability in MYC reveals biphasic E2f1 dose response ► Modeling predicts serum attenuates E2F repression by MYC ► Biphasic expression underlies discrimination of aberrant levels of growth signaling